Liver transplantation from active COVID‐19 donors: Is it ethically justifiable?. Issue 4 (1st June 2022) - Grossi, Alessandra Agnese; Nicoli, Federico; Cardillo, Massimo; Gruttadauria, Salvatore; Tisone, Giuseppe; Ettorre, Giuseppe Maria; De Carlis, Luciano; Romagnoli, Renato; Petrini, Carlo; Grossi, Paolo Antonio; Picozzi, Mario
Abstract: The debate on the opportunity to use organs from donors testing positive for Severe Acute Respiratory Syndrome Coronavirus 2 (SARS‐CoV‐2) in recipients with naïve resolved or active COVID‐19 is ongoing. We aim to present the ethical analyses underlying the decision to perform liver transplantation (LT) in selected patients with resolved or active COVID‐19 in Italy. We used Jonsen, Siegler, and Winslade's Four‐Boxes casuistic method, addressing the four topics considered as constitutive of the essential structure of single clinical cases for their ethical analysis (medical indications, patient preferences, quality of life, and contextual features) to enable decision‐making on a case‐by‐case basis. Based on these topics, we elucidate the meaning and balance among the principles of biomedical ethics. Clinical ethics judgment based on the relation between the risk of acquiring SARS‐CoV‐2 along with its potentially negative effects and the expected benefits of transplant lead to consider LT as clinically appropriate. Shared decision‐making allows the integration of clinical options with the patient's subjective preferences and considerations, enabling a valid informed consent specifically tailored to the patients' individual circumstances. The inclusion of carefully selected SARS‐CoV‐2 positive donors represents an opportunity to offer lifesaving LT to patients who might otherwise have limited opportunities to receive one. COVID‐19 positive donor livers are fairly allocated among equals, and respect for fundamental rights of the individual and the broader community in a context of healthcare rationing is guaranteed.The ethical analysis of the decision to perform LT in selected patients shows that the decision is ethically justifiable.